ChemInform Abstract: M2PO3N (M: Ca, Sr): ortho‐Oxonitridophosphates with β‐K2SO4 Structure Type. Issue 14 (March 2016) - Marchuk, Alexey; Schultz, Peter; Hoch, Constantin; Oeckler, Oliver; Schnick, Wolfgang
Abstract: Ca2 PO3 N (I) and Sr2 PO3 N (II) are prepared by hot press sintering of stoichiometric amounts of PON and CaO or SrO (multianvil apparatus, 7 GPa, 1100 °C, 60 min) or by solid state reaction (N2 ‐filled silica tubes, 1100 °C, 2 h or 24 h, resp.).